Lecturer's Workload (Teaching) Management System - Mohd Aniq, Mohd Said (UTeM, 2009)
Generally, lecturer workload at university includes three major categories which are teaching, research and services. However, the workload depends on the university itself. In Universiti Teknikal Malaysia Melaka (UTeM), there are other workload terms such as supervising, publishing and consultation. This project focuses on the teaching workload among of the FTMK's lecturers. All teaching activities such as material preparation and actual teaching can be defined as teaching workload. Currently, the teaching workload management was done manually in UTeM. Hence, Lecturer Workload (Teaching) Management System was developed in order to automate the processes in teaching workload management. This thesis will explain the processes of developing the Lecturer Workload (Teaching) Management System which includes introduction of the system, literature review and project methodology, system analysis and design, and system implementation.